THE STAGES OF FIRM LIFE CYCLE AND CAPITAL STRUCTURE RATIOS FOR COMPANIES OF INDUSTRY - Mirosław Wasilewski; Joanna Żurakowska (Polityki Europejskie, Finanse i Marketing)
This paper presents research on the dependency between the particular stages of a firm’s life cycle and selected capital structure ratios. The findings are in line with the pecking order theory of capital structure, stating that early stages of a firm’s life cycle should be characterised by the tendency for financing through debt. However, this stands in opposition to both the trade-off theory, and the research conducted on several Polish companies. The enterprises in their stages of introduction and growth were characterised by a substantially lower level of total assets to shareholders' equity ratio in their sources of finance, when compared to those in the shake-out stage. The companies in their growth stage were marked by a significantly higher level in the share of long-term commitments in sources of finance, as compared to the enterprises in their maturity, shake-out and decline stage. Also, the introduction stage showed a significantly higher level in the share of short-term commitments in sources of finance, in comparison with those being in their growth, maturity, and shake-out stage.